Starting from the Same Spot: Exploring Mindfulness Meditation and Student Transitions in the Introductory Health Promotion Classroom - MacQuarrie, Madison; Blinn, Nicole; MacLellan, Samantha; Flynn, Megan; Meisner, Jessie; Owen, Phoebe; Spencer, Becky (Canadian Journal of Education / Revue canadienne de l'éducation, 2021)
The purpose of this research was to explore student perceptions of mindfulness meditation (MM) in an introductory health promotion course, and how the use of MM during class might relate to the transitions experienced by students. Qualitative data collection took place through an online survey and in-person interviews. Data were analyzed using thematic analysis. Four key themes were identified from this research. First, that MM facilitates a sense of peace and calm; second, that MM encourages students to focus; third, MM helps promote student mental health; and finally, MM positively changes the classroom environment. Challenges and recommendations were also described.